2008
DOI: 10.1016/j.pbb.2007.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Actions of 3,4-methylenedioxymethamphetamine (MDMA) on cerebral dopaminergic, serotonergic and cholinergic neurons

Abstract: Abstract3,4-Methylenedioxymethamphetamine (MDMA) is an amphetamine derivative and a popular drug of abuse that exhibits mild hallucinogenic and rewarding properties and engenders feelings of connectedness and openness. The unique psychopharmacological profile of this drug of abuse most likely is derived from the property of MDMA to promote the release of dopamine and serotonin (5-HT) in multiple brain regions. The present review highlights primarily data from studies employing in vivo microdialysis that detail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
98
2
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(102 citation statements)
references
References 99 publications
(114 reference statements)
1
98
2
1
Order By: Relevance
“…Increases in MDMA-induced dopamine and 5-HT release, and the neurotoxicity of 5-HT by MDMA, suggest the involvement of MDMA metabolites (Escobedo et al, 2005;Erives et al, 2008;Colad et al, 2004) and the formation of reactive oxygen species (Erives et al, 2008;Gudelsky and Yamamoto, 2008;Quinton and Yamamoto, 2006). Clarification of the mechanism of drug interactions with MDMA, especially with respect to metabolism and the formation of reactive oxygen species, will require further study.…”
Section: Pharmacodynamic Effects Of Mdma On Dopamine and 5-ht Levels mentioning
confidence: 99%
“…Increases in MDMA-induced dopamine and 5-HT release, and the neurotoxicity of 5-HT by MDMA, suggest the involvement of MDMA metabolites (Escobedo et al, 2005;Erives et al, 2008;Colad et al, 2004) and the formation of reactive oxygen species (Erives et al, 2008;Gudelsky and Yamamoto, 2008;Quinton and Yamamoto, 2006). Clarification of the mechanism of drug interactions with MDMA, especially with respect to metabolism and the formation of reactive oxygen species, will require further study.…”
Section: Pharmacodynamic Effects Of Mdma On Dopamine and 5-ht Levels mentioning
confidence: 99%
“…In this study, the effects were observed inde- stimulates acetylcholine release, although this reported effect appears to be minor in comparison to its effects on 5-HT and dopaminergic receptors [115].…”
Section: Discussionmentioning
confidence: 50%
“…However, we have previously found reductions of brain serotonin transporters, as measured by PET, to be significantly associated with self-reported lifetime MDMA exposure. 19 Finally, concerns regarding the role of other drugs of abuse in the present findings are mitigated by the relationship between extent of prior MDMA exposure and sleep apnea and hypopnea in the current study, the known dose-related neurotoxic effects of MDMA toward brain serotonin neurons, [15][16][17][18] and the fact that serotonin has been previously implicated in OSA. 8 Additional research will be necessary to determine whether sleep abnormalities in MDMA users play a role in subtle cognitive deficits and impulsivity that have previously been identified in this population.…”
Section: Resultsmentioning
confidence: 68%
“…15,16 Studies in animals, including nonhuman primates, have demonstrated that MDMA leads to lasting dose-related and protracted reductions in a variety of brain serotonin axonal markers, and neuroanatomical studies with immunochemical markers suggest that losses of axonal markers are secondary to a distal axotomy of serotonin neurons. 17,18 PET imaging studies using radioligands that bind to serotonin transporters provide evidence that MDMA is also neurotoxic in humans.…”
Section: 4mentioning
confidence: 99%